Swedish copper and financial skullduggery in Amsterdam, 1610-1625 - Lawrence S. Stryker (The Journal of European Economic History (JEEH), 2022)
In 1611 the young Gustav Adolf Vasa ascended the throne of Sweden as Gustav II Adolf. Along with the throne, the king inherited a disastrous war with Denmark, which he ended by signing the onerous Peace of Knäred. The terms included the obligation for Sweden to pay a one million rixdaler reimbursement to redeem the strate- gically important fortress at Älvsborg. With an empty treasury, the king turned to his fellow Protestants in the United Provinces for financial assistance. Fortunately, Sweden possessed one major asset, the largest copper mine in Europe. The crown sent copper ingots to Amsterdam, for security, and borrowed against them. This sparked an intense rivalry as two factions of royal servants in the Netherlands sought to obtain the lucrative monopoly for the sale of copper. On one side there was Louis de Geer, a successful weapons dealer. His faction was defended by F.W. Dahlgren whose twentieth-century biography of the merchant was commissioned by de Geer's descendent, Baron Louis de Geer. The rival faction in- cluded a distinguished nobleman and member of the States Gen- eral, Hugo Muys van Holy who promptly mounted a viscous smear campaign against de Geer and his partner. This rivalry quickly descended into accusations of treason and corruption.
Keywords: 330; Copper market; Dutch; Monopoly; Competition; Conflict; Copper; Swedish; Netherlands; Kupfermarkt; Niederländisch; Monopol; Wettbewerb; Konflikt; Kupfer; Schwedisch; Niederlande